Aid, public sector fiscal behaviour and developing country debt - Simon Feeny; Mark McGillivray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper looks at public sector debt in developing countries, being concerned specifically with the relationship between aid inflows and the public sector borrowing requirement net of aid loans. After examining the public sector budget constraint and various conditions under which aid might lead to an increase in this borrowing, the paper surveys the empirical results of literature on aid and public sector fiscal behaviour. It finds that the results of a number of studies are consistent with aid leading to increases in this borrowing. Further investigation, in the form of econometric analysis of panel data, also points to this outcome. The paper then looks at a number of theoretical scenarios in which aid leads to increases in borrowing net of aid loans. – aid ; borrowing ; debt ; fiscal behaviour
Keywords: O23; H10; 330; Öffentliche Schulden; Entwicklungshilfe; Theorie; Entwicklungsländer